A Review of the Medicinal Plants from the Tragopogon Spp. - Z Bayrami; F Khalighi-Sigaroodi; M Abdollahi; R Rahimi; MH Farzaei; R Hajiaghaee (Institue of Medicinal Plants, ACECR, 2016)
Tragopogon is a genus of Asteraceae family and Lactuceae tribe. Distribution of this genus in different areas resulted to its dietary and feed applications as well as medicinal uses. Different parts of these plants have been used in treatment of stomachache and digestive disorders. In Iranian traditional medicine they used as hemostatic and wound healing agent in nose, ears, lungs, throat, intestine, stomach, and skin bleeding. Reduction of lipid peroxidation and blood lipid level, antioxidant, antileukemic, and antibacterial effects, and healing effect on inflammatory bowel disease are some of evaluated pharmacologic effects of the plants in this genus. Flavonoids, terpenes, saponins, bibenzyl and hydroisocoumarins, phenolic compounds, and strolls are some of detected phytochemicals of these plants that majority of them have been identified through the chemotaxonomic studies. Some tragopogon plants with high antioxidant effect are able to protect the tissues from the inflammatory disorders and inhibit DNA damage in the determined concentrations.